Gas inflows towards the nucleus of the Seyfert 2 galaxy NGC 1667. Issue 4 (2nd February 2017) - Schnorr-Müller, Allan; Storchi-Bergmann, Thaisa; Ferrari, Fabricio; Nagar, Neil M.
Abstract: We use optical spectra from the inner 2 × 3 kpc 2 of the Seyfert 2 galaxy NGC 1667, obtained with the Gemini Multi-Object Spectrograph integral field spectrograph on the Gemini South telescope at a spatial resolution of ≈240 pc, to assess the feeding and feedback processes in this nearby active galactic nucleus (AGN). We have identified two gaseous kinematical components in the emission line profiles: a broader component (σ ≈ 400 km s −1 ) that is observed in the inner 1–2 arcsec and a narrower component (σ ≈ 200 km s −1 ) that is present over the entire field of view. We identify the broader component as due to an unresolved nuclear outflow. The narrower component velocity field shows strong isovelocity twists relative to a rotation pattern, implying the presence of strong non-circular motions. The subtraction of a rotational model reveals that these twists are caused by outflowing gas in the inner ≈1 arcsec, and by inflows associated with two spiral arms at larger radii. We calculate an ionized gas mass outflow rate of M_out ≈ 0.16 M⊙ yr −1 . We calculate the net gas mass flow rate across a series of concentric rings, obtaining a maximum mass inflow rate in ionized gas of ≈2.8 M⊙ yr −1 at 800 pc from the nucleus, which is two orders of magnitude larger than the accretion rate necessary to power this AGN. However, as the mass inflow rate decreases at smaller radii, most of the gas probably will not reach the AGN, but accumulate in the inner few hundred parsecs. This will create a reservoir of gas that can trigger the formation of new stars.